Negara dalam Islam: Simbolisme Integrasi Agama dan Negara (al-Din wa al-Dawlah) - Muhammad Ichsan; Desi Kurnia Sari; Hasyimsyah Nasution; Mardian Idris Harahap (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2026)
The concept of the state in Islam is one of the most fundamental yet controversial discourses in Islamic political thought. This article examines the symbolic relationship between religion (al-din) and the state (al-dawlah) from historical, theological, and comparative perspectives. The objective of this study is to analyze the conceptual construction of the Islamic state, map the intellectual debates between the paradigms of integration and separation, and evaluate their relevance within the context of contemporary Muslim politics. The findings indicate that the relationship between al-din wa al-dawlah is not a single monolithic entity but rather a spectrum encompassing models of symbolic theocracy, Islamic democracy, and a civil state grounded in Islamic values. The integration paradigm, represented by al-Mawardi and Ibn Khaldun, emphasizes divine legitimacy as the foundation of political authority. In contrast, the functional separation paradigm, popularized by Ali Abd al-Raziq and later reformulated by Fazlur Rahman, positions religion as a source of moral guidance without requiring it to function as a formal instrument of the state. The study concludes that the concept of al-din wa al-dawlah is more appropriately understood as a dynamic and dialectical relationship that continues to evolve in response to changing socio-political contexts, rather than as a fixed and ahistorical formula